Long-Term Exposure to Ambient Ozone and Progression of Subclinical Arterial Disease: The Multi-Ethnic Study of Atherosclerosis and Air Pollution - Wang, Meng; Sampson, Paul D.; Sheppard, Lianne E.; Stein, James H.; Vedal, Sverre; Kaufman, Joel D. (Environmental health perspectives, 2019)
Long-term ozone ([Formula: see text]) exposure is associated with cardiovascular mortality, but little is known about the associations between [Formula: see text] and subclinical arterial disease. We studied the longitudinal association of exposure to [Formula: see text] and progression of key subclinical arterial markers in adults: intima-media thickness of common carotid artery ([Formula: see text]), carotid plaque (CP) burden, and coronary artery calcification (CAC). CAC was measured one to four times at baseline and at follow-up exams (1999–2012) by computed tomography (CT) in 6,619 healthy adults, recruited at age 45-84 y without cardiovascular disease (CVD), over a mean of 6.5 y (standard deviation: 3.5 y). [Formula: see text] and CP burden were quantified in 3,392 participants using carotid artery ultrasound imaging acquired over a mean of 9 y (1.7 y). Over 91% and 89% participants had at least one follow-up [Formula: see text] and CAC measurement, respectively. Residence-specific [Formula: see text] concentrations were estimated by a validated spatiotemporal model spanning from 1999 to 2012. This model relied on comprehensive monitoring data and geographical variables to predict individualized long-term average concentrations since baseline. Linear mixed models and logistic regression model were used to evaluate relationships of long-term average exposure to [Formula: see text] with longitudinal change in [Formula: see text], CAC, and CP formation, respectively. Mean progression rates of [Formula: see text] and CAC were [Formula: see text] and [Formula: see text]. CP formation was identified in 55% of the subjects. A [Formula: see text] increase in long-term average [Formula: see text] exposure was associated with a [Formula: see text] [95% confidence interval (CI): 1.4, 9.7] greater increase in [Formula: see text] over 10 y. A [Formula: see text] increase in [Formula: see text] was also associated with new CP formation [odds ratio (OR): 1.2 (95% CI: 1.1, 1.4)] but not CAC progression [[Formula: see text] (95% CI: [Formula: see text], 2)]. Associations were robust in the analysis with extended covariate adjustment, including copollutants, i.e., nitrogen oxides ([Formula: see text]) and particulate matter with diameter [Formula: see text] ([Formula: see text]). Over almost a decade of follow-up, outdoor [Formula: see text] concentrations were associated with increased rate of carotid wall thickness progression and risk of new plaque formation, suggesting arterial injury in this cohort. https://doi.org/10.1289/EHP3325.